Reseña de Deutscher, Guy (2010).Through the Language Glass. Why the World Looks Different in Other Languages. - José Luis Guijarro Morales (Pragmalingüística)
Reseña de Deutscher, Guy (2010). Through the Language Glass. Why the World Looks Different in Other Languages.